Técnicas de energia elétrica sustentável aplicadas em edificações - Motta, Rodolfo Rafael Berino da [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
One of the majors concerns in society today is to decrease the environmental impact caused by human activities and natural resource exploration. From this need to be more careful with the environment arose, in the field of civil construction, the term sustainable building. Projects that use natural resources rationally, without ceasing to bring comfort and functionality for customers, are becoming more a reality. This paper presents the share of electric energy in a sustainable building, with the analysis of the available renewable energies used in a project, presentation of new constructive techniques and technologies that are constantly emerging to achieve greater energy efficiency, with an appropriate use of energy received, also a decrease of the energy consumed by some devices present in a residence or business

Uma das maiores preocupações da sociedade atual é a diminuição do impacto ambiental provocado pelas atividades humanas e exploração de recursos naturais. Dessa necessidade de um maior cuidado com o meio-ambiente surgiu, no meio da construção civil, o termo edificação sustentável. Projetos que usam racionalmente os recursos naturais, sem deixar de gerar conforto e funcionalidade para os clientes, se tornam cada vez mais uma realidade. Este trabalho apresenta a participação da energia elétrica em uma edificação sustentável, com a análise das energias renováveis existentes utilizadas em um projeto, apresentação de novas técnicas construtivas e tecnologias que surgem constantemente para se alcançar uma maior eficiência energética, com um uso adequado da energia recebida, além de uma diminuição da energia consumida por alguns aparelhos presentes em uma residência ou empresa
Keywords: Edifícios sustentáveis - Projetos e construção; Energia - Fontes alternativas; Energia eletrica - Consumo; Impacto ambiental; Energia elétrica - Racionamento; Recursos naturais renovaveis; Environmental impact; Sustainable Building; Energy Efficiency